Analisis Komposisi Visual dalam Serial Netflix The Umbrella Academy Season 4 : Pendekatan Sinematik terhadap Narasi Visual - Hendi Thamrin (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the visual composition in the fourth season using a cinematic approach, focusing on how elements such as framing, lighting, color, camera movement, and spatial arrangement support the narrative and character development. The Umbrella Academy is known for its unique storytelling and strong visual style. The fourth season, which also serves as the final season, went viral on social media and entered Netflix Indonesia’s Top 10 list. The method used is a qualitative approach with visual analysis. Each episode is examined to identify how visual elements are strategically used to convey themes and emotions. Theories of cinematography and visual composition serve as the foundation for this analysis. The findings of this study are expected to contribute to the field of Visual Communication Design, particularly in the strategic use of visual elements to enhance storytelling. In addition to enriching academic literature, the results may serve as practical references for filmmakers, visual designers, and producers in creating impactful visual content. This study is also intended for publication in a Sinta-indexed journal or an international journal focusing on film studies and visual design.